Basic Human Duties from a Qur’anic Perspective - Deden Hilmansah; Komarudin (Jurnal test, 2024)
Human perfection is a depiction of God's greatness that humans are not only equipped with physical perfection but also psychic which makes them different from other creatures. Humans are endowed with reason in order to be able to distinguish between good and bad and to be able to analyse everything related to the universe which at its peak becomes a complete person so that humans carry out the tasks and responsibilities imposed by God on them to be fulfilled, guarded and maintained as well as possible. But in reality, many humans have forgotten this mandate, this can be seen from the development of humans who are increasingly far from their nature as perfect beings and deviate from their duties as humans. This paper aims to explain the nature of man and the main duties of man from the perspective of the Qur'an. Through descriptive method by utilising literature study, it can be concluded that the nature of man in the perspective of the Qur'an is the most perfect creature because it consists of body and soul, which has reason and lust and humans are Biological, Psychological and Sociological creatures. Then the main task of humans in the perspective of the Qur'an is as servants of Allah and as caliphs on earth, humans are given this task because humans are the most perfect creatures and have advantages over other creatures.